DOSIMETRIC COMPARISON OF INTENSITY-MODULATED RADIATION THERAPY (IMRT) AND VOLUMETRIC-MODULATED ARC THERAPY (VMAT) IN RECTAL CANCER PATIENTS: A COMPREHENSIVE ANALYSIS - SHAFIQUE, S; KHAN, K; BAIDAR , T; OKASHA, M (Biological and Clinical Sciences Research Journal, 2024)
This study aimed to conduct a thorough dosimetric comparison between two advanced radiotherapy techniques, Intensity-Modulated Radiation Therapy (IMRT) and Volumetric-Modulated Arc Therapy (VMAT), to ascertain the superior modality in terms of dose distribution and organ-at-risk sparing for rectal cancer patients. Thirty-three patients with ECOG performance status 1, aged between 18 to 60 years, diagnosed with Stage II to III rectal cancer, were included in this prospective study. Each patient underwent treatment planning with IMRT and VMAT techniques using Varian system simulation computed tomography scans. The dosimetric analysis encompassed the evaluation of target volume dose homogeneity, conformity, and doses to at-risk organs. The dosimetric comparison was conducted utilizing seven-field IMRT and dual arc VMAT plans. Statistical analysis was performed using paired t-tests and SPSS 20 software. Treatment plan constraints adhered to the RTOG 9406 guidelines, ensuring adequate planning target volume (PTV) coverage, homogeneity index, conformity index, and dose limits for organs at risk, including small bowel V20 (<200cc), bladder V45 (<21Gy), and femoral head V50 (≤30 Gy). Volumetric arc therapy plans demonstrated superior dose homogeneity to fixed-field intensity-modulated plans (p-value = 0.04), particularly in femoral head dose-limiting toxicity (p-value = 0.00). However, intensity-modulated therapy exhibited equivalent or superior performance in other evaluated parameters. Our findings suggest that while VMAT offers advantages in PTV coverage homogeneity and femoral head dose-limiting toxicity, IMRT remains competitive and potentially preferable in certain dosimetric aspects. The choice between IMRT and VMAT should be carefully considered based on individual patient characteristics and treatment goals. This comprehensive dosimetric comparison contributes valuable insights into optimizing radiotherapy planning for rectal cancer patients, potentially guiding clinical decision-making and improving treatment outcomes.